2021
DOI: 10.5114/ppn.2021.106818
|View full text |Cite
|
Sign up to set email alerts
|

Early life trauma – review of clinical and neurobiological studies

Abstract: Purpose: Psychological trauma is a significant risk factor for physical and mental health development distortion. This paper presents the results of longitudinal epidemiological surveys and naturalistic observations. It also reviews the results of the most important neurobiological findings in the field of impact of early life trauma on cognitive and emotional development, and the structure and functions of the brain. Views: Trauma is defined as subjective experiences that overwhelm a person's ability to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The stress generated by chronic exposure to violence produces negative effects on brain circuits that link subcortical and cortical structures such as the amygdala, hippocampus, and prefrontal lobes. These effects are expressed as difficulties in responding appropriately to social context (LeMoult et al, 2020; Rok-Bujko, 2021), and have been found in the cognitive profiles of child victims (Barrera-Valencia et al, 2017; Noriega et al, 2021; Pellizzoni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress generated by chronic exposure to violence produces negative effects on brain circuits that link subcortical and cortical structures such as the amygdala, hippocampus, and prefrontal lobes. These effects are expressed as difficulties in responding appropriately to social context (LeMoult et al, 2020; Rok-Bujko, 2021), and have been found in the cognitive profiles of child victims (Barrera-Valencia et al, 2017; Noriega et al, 2021; Pellizzoni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman & Charney, 2001). When these brain regions are affected, individuals struggle to appropriately respond to stressful situations, exhibiting executive functioning and social cognition difficulties (Londoño-Arredondo et al, 2008; Rok-Bujko, 2021). At a cognitive level, executive functions are involved in the generation, control, regulation, and adjustment of behaviors (Tirapu-Ustárroz et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los fallos atencionales desencadenan también en dificultades para codificar, almacenar y evocar información verbal y no verbal, hecho que corresponde con la evidencia sistemática de afectaciones estructurales en los hipocampos (Rok-Bujko, 2021;Wade et al, 2022). El actual estudio presenta resultados similares a los evidenciados en la literatura, identificando dificultades en atención visual y memoria verbal y no verbal.…”
Section: Discussionunclassified